1997
DOI: 10.1007/s11663-997-0083-6
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic extraction of iron(III) at higher concentrations in D2EHPA-TBP mixed solvent systems

Abstract: The extraction of iron(III) from chloride solutions at macrolevel concentration by different solvents such as tri-n-butyl phosphate (TBP), di(2-ethylhexyl) phosphoric acid (D2EHPA), and their mixture in various proportions has been investigated at different acid concentrations. The synergistic extraction of iron(III) with a mixture of TBP and D2EHPA was studied and the results were compared with that of the extraction by individual solvent alone. An increase in the concentration of the synergist, TBP, in the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(17 citation statements)
references
References 22 publications
2
15
0
Order By: Relevance
“…Therefore, the mixture of 1 M D2EHPA and 1 M TBP was employed in further experiments. In our experimental range, the solvent extraction reaction of iron by the mixture of D2EHPA (RH) and TBP (L) can be represented as 13,14 :…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the mixture of 1 M D2EHPA and 1 M TBP was employed in further experiments. In our experimental range, the solvent extraction reaction of iron by the mixture of D2EHPA (RH) and TBP (L) can be represented as 13,14 :…”
Section: Resultsmentioning
confidence: 99%
“…11,12 An alternative method to overcome this difficulty has been developed by employing the mixture of D2EHPA and TBP for the extraction of Fe. [13][14][15][16] It was found that the mixture of D2EHPA and TBP exhibited better extraction ability than single extractant 13,14 and the stripping of Fe(III) from the mixture of D2EHPA and TBP was easier than that from D2EHPA alone. 15,16 Although the use of mixture of D2EHPA and TBP can increase the extraction and stripping efficiency of Fe, it is still difficult to strip most of Fe when the concentration of loaded iron is high.…”
Section: Introductionmentioning
confidence: 99%
“…Kinetic determinations are necessary to understand the extraction mechanism. However, the heterogeneous nature of SX reactions makes kinetic determinations challenging [2], especially at high concentrations which are relevant to industrial applications [1,5,6]. The preferred tool for SX kinetic investigations has been the Lewis cell [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…[13,15] In order to overcome these difficulties, sevtime was longer than 5 minutes. After phase separation, the eral researchers [6,[19][20][21] and the present authors [22,23] have concentration of iron(III) in the raffinate was analyzed by reported synergistic solvent extraction and an associated the SnCl 2 reduction method. [24] The distribution coefficient improvement in iron(III) stripping using various mixed (D) was obtained from the ratio of the equilibrium concentraextractants.…”
Section: Introductionmentioning
confidence: 99%